Marketing strategy: annd competitive positioning - Hooley, Graham; Saunders, John; Piercy, Nigel F.; Nicoulaud, Brigitte (Singapore, 2008)
The book focuses on creating and sustaining superior performance in the marketplace.
Keywords: Marketing management- case studies